Incidence and Impact of COVID-19 in MS: A Survey From a Barcelona MS Unit. Issue 2 (27th March 2021) - Sepúlveda, Maria; Llufriu, Sara; Martínez-Hernández, Eugenia; Català, Martí; Artola, Montse; Hernando, Ana; Montejo, Carmen; Pulido-Valdeolivas, Irene; Martínez-Heras, Eloy; Guasp, Mar; Solana, Elisabeth; Llansó, Laura; et al.
Abstract : Objective: To investigate the incidence of coronavirus disease 2019 (COVID-19) in a single-center cohort of patients with MS and to explore the contribution of their comorbidities and therapies to the outcome. Methods: A cross-sectional mixed-method study was conducted involving an email-based, self-administered questionnaire sent on May 21, 2020, to 586 patients with MS followed at the MS Unit of Hospital Clinic, University of Barcelona, along with telephone interview, and review of electronic medical records until June 18, 2020. The cumulative incidence of confirmed COVID-19 (positive PCR or antibody test) and all COVID-19 cases (confirmed and suspected) from the start of the pandemic was compared with the population estimates for Barcelona. Results: A total of 407 patients (69.5%) completed the survey. Most of the responders (67%) were female. The responders had a median age of 48 years (range 19–86), relapsing-remitting disease (84%), at least 1 comorbidity (45%), and were on disease-modifying therapy (DMT; 74.7%). COVID-19 was confirmed in 5 patients (1.2%) and suspected in 46 (11.3%). The cumulative incidence of confirmed COVID-19 cases was similar to that of the general population but was almost 2-fold higher when all cases were considered ( p < 0.001). Six patients (11.7%) were hospitalized, of which 5 had good recovery and 1 died. Hospitalized patients were more frequently male, had diabetes and had progressive forms of MS ( p < 0.05). DMT was not associated with the risk of infection or the outcome. Conclusions: In the studied MS cohort, the incidence of COVID-19 was higher than that of the general population; however, most patients did not require hospitalization and had a good outcome despite the frequent presence of comorbidities and treatment with DMT.